2014
DOI: 10.1530/ec-14-0083
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and ischemic heart disease: double jeopardy with regard to depressive mood and reduced quality of life

Abstract: The aim of this study was to test i) whether patients having diabetes and ischemic heart disease (IHD), i.e., patients suffering from two chronic diseases, demonstrate a higher degree of chronic stress when compared with patients suffering from IHD alone, and ii) whether suffering from the two chronic diseases results in an elevation in specific elements of the chronic stress concept. A total of 361 participants with IHD were included, of whom 47 suffered from concomitant diabetes. Stress was measured by press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Two-week morbidity rate is a strong predictor of HRQOL [ 10 ]. Chronic diseases are associated with lower HRQOL [ 23 , 24 ]. In our study, migrants were more likely to have reported recent two-week morbidity or chronic diseases than local urban residents.…”
Section: Discussionmentioning
confidence: 99%
“…Two-week morbidity rate is a strong predictor of HRQOL [ 10 ]. Chronic diseases are associated with lower HRQOL [ 23 , 24 ]. In our study, migrants were more likely to have reported recent two-week morbidity or chronic diseases than local urban residents.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the increase in the number of studies analysing the negative association between HRQoL and diabetes in the last decade, the literature comparing the HRQoL of people with and without diabetes remains very scarce as well as the analyses of the potential factors involved in this negative effect, usually limited to the role of cardiovascular disease, but ignoring the one due to cardiovascular risk factors [ 16 , 18 , 19 ]. Moreover, no studies have compared the HRQoL in people with and without diabetes using a representative sample of the general population, with the use of advanced statistical methods appropriate for this purpose and identifying the dimension of HRQoL (mobility, self-care, daily activities, pain/discomfort, or anxiety/depression) which are affected the most.…”
Section: Introductionmentioning
confidence: 99%
“…Em um estudo realizado também com pacientes diabéticos (DM) e portadores de doença cardíaca isquêmica (DCI); o qual utilizou o SF-36 associado ao Major Depression Inventory (MDI), WHO-5 Well-being Index e a clinical stress signs (CSSs) scale; observou-se que essa combinação patológica está associada com o aumento de sintomas depressivos, baixa qualidade de vida e saúde mental. 13 Uma vasta gama de questionários validados e confiáveis ou medidas de resultados relatados pelo paciente estão disponíveis para avaliação de QV em pacientes com doenças graves, com risco de vida, incluindo instrumentos genéricos de estado de saúde, instrumentos genéricos de doenças, instrumentos específicos de doenças e instrumentos combinados, como o Sistema de Informação de Medição de Resultados Relatados pelo Paciente (PROMIS). 14 A QV em pacientes idosos se encontra limitada, mas o comprometimento agressivo DM, com seu envolvimento em toda circulação e suas implicações sistêmicas acentuam as limitações destes pacientes.…”
Section: Discussionunclassified